PENYISIHAN WARNA PADA LIMBAH CAIR INDUSTRI SASIRANGAN DENGAN ADSORPSI KARBON AKTIF - Andy Mizwar; Nurin Nisa Farah Diena (Universitas Lambung Mangkurat, 2012)
Dye removal from sasirangan textile wastewater by using commercially available activated carbon in a batch reactor was studied. This research explores the effect of activated carbon dosing and contact time on the condition of constant pH and stirring speed toward the effectiveness of dye removal. The results showed that the effectiveness of dye removal of 20.75% - 39.16% with the optimum contact time of 60 minutes and the pattern of dye adsorption by activated carbon in this study were more likely to follow the model of Langmuir Isotherms with a maximum adsorption capacity of 29.412 mg/g.